2013
DOI: 10.4236/ape.2013.34029
|View full text |Cite
|
Sign up to set email alerts
|

Techniques Used by Elite Thai and UK Muay Thai Fighters: An Analysis and Simulation

Abstract: Background: Muay Thai is a combat sport growing in international popularity. Previous research has highlighted marked jurisdictional differences in the judging systems employed, but no studies have compared techniques used by fighters across geographic regions or have been on how these might be a function of the different judging systems employed. This paper aimed to address this issue by examining differences in technique selection and application between Thai and UK Muay Thai fighters using notational analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Muay Thai is a combat sport that originated in Thailand, referred to as "the art of 8 limbs." Competitors can kick, punch, knee, elbow, and clinch their opponents (19,20,26). A Muay Thai bout can last up to 5 rounds of 3 minutes each but is sometimes shortened depending on the competitors' competence and experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muay Thai is a combat sport that originated in Thailand, referred to as "the art of 8 limbs." Competitors can kick, punch, knee, elbow, and clinch their opponents (19,20,26). A Muay Thai bout can last up to 5 rounds of 3 minutes each but is sometimes shortened depending on the competitors' competence and experience.…”
Section: Introductionmentioning
confidence: 99%
“…The roundhouse kick can be an effective technique when actioned by a high hip angular velocity; Diniz et al (10) found that when comparing the roundhouse kick technique, used in other striking-based martial arts, with Muay Thai, the angular velocity of the hip is greater and can produce a higher impact, causing destructive damage to gain points or incapacitate an opponent. The Teep kick (front push kick) also has similar efficacy; being one of the most used techniques in Muay Thai for attacking and countering attacks from the opponent, showing benefits from increasing competitors kicking performance impact power (14,19,22). Vagner et al (27) identified the Teep kick to be highly effective in close quarter combat, and the need for increased destructive impact was key to successful performances.…”
Section: Introductionmentioning
confidence: 99%
“…Muay Thai (Thai boxing) is a ‘cultural export’ and the most popular sport in Thailand. The sport has a great influence on the world of combat sports and commercial trends [ 29 ]. Thai boxing is termed an ‘eight-limb’ martial art, with practitioners using eight points of contact with the opponent (i.e., fists, elbows, knees, and feet).…”
Section: Introductionmentioning
confidence: 99%
“…Thai boxing is termed an ‘eight-limb’ martial art, with practitioners using eight points of contact with the opponent (i.e., fists, elbows, knees, and feet). Furthermore, it includes grappling techniques (involving takedowns and clinch) [ 1 , 29 ]. Brazilian jiu-jitsu (BJJ) is the flagship ground fighting sport developed in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…O boxe internacional tem sido o principal esporte de combate televisionado em exposição na mídia em todo o mundo (MYERS et al, 2013). No entanto, nos últimos anos, outros esportes de combate têm desafiado esse monopólio.…”
Section: Introductionunclassified